ANALISIS STRATEGI DEFERENSIAL TERHADAP KEPUASAN KONSUMEN PADA PT. POS CABANG SANGATTA - Devi Lestari; Saiful; Juwita Aprilla (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2020)
This study aims to analyze the differential strategy on customer satisfaction at PT. Sangatta Post. The research method used is descriptive method by obtaining data from observations, documentation, interviews and questionnaires. From the results of the analysis of the discussion conducted by the author, the results of this study indicate that the differentiation strategy consisting of product differentiation, service differentiation, personnel differentiation and channel differentiation has a positive and significant effect on customer satisfaction